Thermal Degradation and Fourier Transform Infrared Spectroscopy Characterization of Polypropylene under Multiple Mechanical Recycling Cycles - Zakaria, Siti Hajar; Asman, Saliza (Enhanced Knowledge in Sciences and Technology, 2026)
This study investigates the effect of repeated mechanical recycling on the thermal and chemical properties of polypropylene (PP). Virgin PP (v-PP) was subjected to three recycling cycles (r1-PP, r2-PP, r3-PP) through repeated melting. Thermal degradation behavior was analyzed using thermogravimetric analysis (TGA), while chemical structural changes were examined using Fourier transform infrared spectroscopy (FTIR). TGA result showed a single step degradation for all samples. The onset degradation temperature increased from 418.73°C (v-PP) to 440.64°C (r2-PP), indicating improved thermal stability after initial recycling cycles, but decreased to 414.62°C in r3-PP due to stabilizer depletion and chain scission. Weight loss remained high (~97–98 wt%) with minimal residue (~1–2 wt%). FTIR analysis revealed increased intensity of C–H, C–C, and C=O functional groups in recycled samples, indicating oxidative degradation and structural modification. These findings suggest that limited recycling cycles do not significantly degrade PP performance, while excessive recycling reduces thermal stability.